Treatment of a subchondral cystic‐like lesion in the distal scapula with a translesional bone screw in a horse. (3rd March 2020) - Corraretti, G.; Meulyzer, M.; Simon, O.
Summary: A 2‐year‐old French Warmblood stallion was presented for lameness investigation. The diagnostic procedures identified the reason for lameness as being a subchondral cystic‐like lesion (SCL) in the glenoid cavity of the scapula. The horse was surgically treated with a translesional 4.5 mm cortical bone screw inserted through the SCL under radiographic guidance. Sixty days after surgery, the horse was sound and the SCL showed significant radiographic signs of healing. Radiographs obtained 180 days after surgery showed further radiographic healing, with the SCL presenting a radiodensity similar to the surrounding bone. At 4 years post‐operative follow‐up, the horse is sound and competing successfully as a 6‐year‐old in Concours de Saut International (CSI) competitions.